Smoothed finite element method for topology optimization involving incompressible materials. Issue 12 (1st December 2016) - Li, Eric; Chang, C.C.; He, Z.C.; Zhang, Zhongpu; Li, Q.
Abstract : It is well known that the finite element method (FEM) suffers severely from the volumetric locking problem for incompressible materials in topology optimization owing to its numerical 'overly stiff' property. In this article, two typical smoothed FEMs with a certain softened effect, namely the node-based smoothed finite element method (NS-FEM) and the cell-based smoothed finite element method, are formulated to model the compressible and incompressible materials for topology optimization. Numerical examples have demonstrated that the NS-FEM with an 'overly soft' property is fairly effective in tackling the volumetric locking problem in topology optimization when both compressible and incompressible materials are involved.